Natural browsing repellent to protect Scots pine Pinus sylvestris from European moose Alces alces - Lindmark, Matilda; Sunnerheim, Kerstin; Jonsson, Bengt-Gunnar (Forest Ecology and Management, 2020)
A major problem within forestry is winter browsing on young Scots pine (Pinus sylvestris) by European moose (Alces alces). Moose are selective foragers and make foraging decisions on many scales, for example, they avoid trees with high levels of plant defensive compounds, which reduce digestibility. Bark extract from Norway spruce (Picea abies) is known to have high levels of such defensive compounds. The aim of this study was to evaluate the effects of Norway spruce bark extract as a repellent to European moose. Spruce bark was extracted in a conventional way with ethanol as the solvent, creating a solution that was applied to the apical leader of young pine trees in planted forests. In two field trials in northern Sweden (winter 2017–2018 and winter 2018–2019), the apical leader of young pine trees (height 1–2.5 m) were sprayed with bark extract from Norway spruce. A total of 5247 pine trees were included in the study. The field trials showed that spruce bark extract lowered the number of browsed apical leader of pine trees, and directed moose to browse less valuable lateral shoots, and neighboring trees. During the first field trial, apical leaders were treated every second meter along transects with a concentration of the spruce bark extract of 2.8% by dry weight. The level of browsed apical leaders changed from 15.1% to 6.8% of all apical leaders. During the second field trial, apical leaders were treated in circular plots, in which all main stems inside the circle were treated with a concentration of the spruce bark extract of 5.0% by dry weight. The level of browsed apical leaders changed from 19.5% to 4.7% of all apical leaders. Hence, results show that spruce bark extract (a non-toxic forest byproduct) can function as an efficient repellent. The bark extract can control browsing to a level that is considered acceptable – generally a maximum of 5% of all apical leaders browsed every year. This would result in approximately 7 out of 10 trees, in treated small scale areas, having unbrowsed apical leaders ...